PEMAKAIAN BAHASA REPORTER SEPAK BOLA DI RADIO - Suhartono Suhartono; Basuki Basuki (CARAKA, 2015)
The objectives of this research are (1) to describe the language variations that are used by football reporter on the radio and (2) to describe the background of the occurrence of language football variation on the radio. This research belongs to descriptive qualitative. The data in this research were in the form of particular terms and sentence that were used by football reporter in the radio. The source of the data was the language used by the football reporter. The instrument in this research was the own research that is armed with a set of science concept related to the problem of the research. The data collecting technique that was used was seen method, and take note technique was the continuation technique that was used in applying see method. The data analysis technique that used in this research were unified method and then continued with selecting specific element and circuited appeal technique. The method of presenting the result of the analysis used informal presentation method. The result of this research can be seen as follows. (1) The language variations that were used by football reporter on the radio were classified into three types, they were morphological variation, lexical variation, and syntax variation. (2) The background that influenced language variations of football reporter on the radio were time, place, the situation of football match, people that involved in the speech, referred to the form and the content of speech of football reporter, referred to the intonation, way, the spirit when the message was delivered, referred to the line of spoken language, referred to the norm or rule of interacting, and the oral delivery form of football reporter on the radio.